2018
DOI: 10.3390/d10020043
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Conservation of Cave-Dwelling Bats in the Brunca Region of Costa Rica

Abstract: The Brunca region in Costa Rica contains the largest number of caves in the country, yet the diversity and distribution of bat species within those caves is currently unknown. Without this information, it is not possible to assess changes in populations and assemblages that may indicate severe damages to these critical roosting habitats, and to take evidence-based conservation actions. We present the first study to describe the diversity of cave-dwelling bat species in the Brunca region of Costa Rica in a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
3
13
0
1
Order By: Relevance
“…In the three localities, the momoopid species P. fulvus was particularly abundant, and although the characteristics of the caves did not allow us to determine the size of their populations, we observed that in each case there were thousands of individuals. In the study area P. gymnonotus and P. fulvus are quite similar to each other (Figure 2), Parque Estatal Agua Blanca has been until now the locality with the largest number of specimens collected in México and most of Central America; only Deleva and Chaverri (2018) report a bigger roost for this species in Costa Rica. This locality is a protected natural area of 2,025 ha with tropical evergreen forest as the dominant vegetation type (Castro-Luna et al 2007;Vargas 2012).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In the three localities, the momoopid species P. fulvus was particularly abundant, and although the characteristics of the caves did not allow us to determine the size of their populations, we observed that in each case there were thousands of individuals. In the study area P. gymnonotus and P. fulvus are quite similar to each other (Figure 2), Parque Estatal Agua Blanca has been until now the locality with the largest number of specimens collected in México and most of Central America; only Deleva and Chaverri (2018) report a bigger roost for this species in Costa Rica. This locality is a protected natural area of 2,025 ha with tropical evergreen forest as the dominant vegetation type (Castro-Luna et al 2007;Vargas 2012).…”
Section: Discussionsupporting
confidence: 55%
“…Pteronotus gymnonotus is an obligate cave-dweller bat. In Costa Rica colonies have been reported with more than 500 individuals in several karstic caves (Deleva and Chaverri 2018); also large assemblages of many thousands of individuals have been observed in karstic localities in northeastern Brazil (Rocha et al 2011;Feijó and Rocha 2017;Vargas-Mena et al 2018). In México, this species is not abundant, with only very few specimens collected in karstic caves in the Parque Estatal Agua Blanca, El Volcán de los Murciélagos and in the Grutas de Martínez de la Torre (Guzmán-Soriano et al 2013;this paper).…”
Section: Discussionmentioning
confidence: 99%
“…Caves are reservoirs for exceptional levels of endemic and threatened species, very high levels of genetic uniqueness, and they harbor unconventional taxa such as blind fishes, crustaceans, worms, and many other groups, including bats (Medellín et al 2017). These ecosystems enclosed unique features for housing bats such as the complete or partial absence of light, constant temperature, and high air humidity (Deleva and Chaverri 2018).…”
Section: Two Caves In Western Honduras Are Important For Bat Conservamentioning
confidence: 99%
“…Caves are also considered as a complex system with a variety of microclimates and roosting conditions for bats (Rodríguez-Durán 2009;Furey and Racey 2016). In other cases, bats are so abundant that they can significantly modify the caves by altering their microclimate conditions and providing important amounts of guano, which is an essential food source for trophic chainsin most caves (Deleva and Chaverri 2018). In return, caves provide to bats a refuge from predators, inconstant weather, and a critical venue for social interactions, reproduction, hibernation, roosting and even alimentation (Furey and Racey 2016).…”
Section: Two Caves In Western Honduras Are Important For Bat Conservamentioning
confidence: 99%
See 1 more Smart Citation